Makna Khashyah dalam Al-Qur’an: Analisis Kritis atas Emosi Dasar dalam Psikologi Islam - Jarman Arroisi; Abdul Rohman; Harits Mu’tasyim; Khoiruddin Abdullah; Adrian Syahidu (AL QUDS : Jurnal Studi Alquran dan Hadis, 2022)
The Meaning of Khashyah in Al-Qur'an: Critical Analysis of Basic Emotions in Islamic PsychologyFear is something that is human nature. Fear that is processed properly will be able to affect human psychic growth. The feeling of fear in Islam is called al-khashyah which has been mentioned many times in the Qur'an and by previous scholars. This paper aims to discuss the meaning of k hasyah in the Qur'an and its analysis in the perspective of Islamic psychology. This paper is in the type of literature review with the main reference source being the Holy Qur'an and its interpretations and books related to Khasyah. This paper is a qualitative research with semantic method used by the author to find the meaning of the Khashyah in the Qur'an, and then it will be analysed critically based on the frame of Islamic psychology. The results of this study indicate that the Qur'an explains a lot about the Khasyah in various derivations of its form, so that the Khasyah itself has various meanings. However, the essence of the meaning of Khashyah is the fear of Allah as a symbol of the perfection of one's faith. Knowledge is an important factor that can direct fear in the right path and direction. Fear that is guided by knowledge will be able to grow the mental health of its owner, in the form of good ethics, the spirit of worship, doing good deeds, and being far from lust. Thus, khasyah, faith, and knowledge are three interrelated things